Contributing factors of mortality in Prader–Willi syndrome. Issue 2 (19th December 2018) - Proffitt, Jennifer; Osann, Kathryn; McManus, Barbara; Kimonis, Virginia E.; Heinemann, Janalee; Butler, Merlin G.; Stevenson, David A.; Gold, June‐Anne
Abstract : Prader–Willi syndrome (PWS) is a multi‐system disorder resulting from a lack of paternal gene expression in the 15q11.2‐q13 region. Using databases compiled through response questionnaires completed by families known to the Prader‐Willi Syndrome Association (USA), this study tested the hypothesis that PWS genetic subtype, BMI, age of diagnosis, clinical symptoms, and growth hormone treatment differ among deceased and living individuals with PWS. Categorical and continuous variables were compared using chi‐square and two‐group t tests, respectively. Deceased individuals had higher rates of clinical features, including increased weight concerns, heart problems, sleep apnea, other respiratory complications, diabetes, osteoporosis, high pain tolerance, and severe skin picking, when compared to living individuals. Meanwhile, living individuals had higher rates of growth hormone use and early puberty. Obesity and subsequent consequences are the primary contributors to increased mortality in PWS. Additional emphasis on areas to decrease mortality is needed.